1985
DOI: 10.1111/j.1440-169x.1985.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Competence to Maturation‐inducing Hormone. I. Breakdown of Germinal Vesicles of Small Oocytes in Starfish, Asterina pectinifera*

Abstract: 1-Methyladenine (1-MeAde) is the endogenous maturation-inducing substance (MIS) in starfish. However. small oocytes have no competence to 1-MeAde even at the concentration of 10V'M. Furthermore, when they were injected with cytoplasm of fully-grown (large) and maturing (1-MeAdetreated) oocytes, known to contain maturation-promoting factor (MPF), they did not undergo germinal vesicle breakdown (GVBD). On the other hand, germinal vesicles (GV) of the small oocytes underwent nuclear breakdown when the small oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…I t could be thus concluded that a proportion of about 40% of growing cytoplasm in the combined cells is sufficient to counteract MPF activity. These results are in full agreement with observations in growing starfish oocytes (Bulet et al, 1985). GVBD in growing oocytes of this species is not induced by a n injection of maturing cytoplasm, known to contain MPF, but only by fusion with maturing oocytes.…”
Section: Nucleo-cytoplasmic Relationships Duringsupporting
confidence: 92%
See 1 more Smart Citation
“…I t could be thus concluded that a proportion of about 40% of growing cytoplasm in the combined cells is sufficient to counteract MPF activity. These results are in full agreement with observations in growing starfish oocytes (Bulet et al, 1985). GVBD in growing oocytes of this species is not induced by a n injection of maturing cytoplasm, known to contain MPF, but only by fusion with maturing oocytes.…”
Section: Nucleo-cytoplasmic Relationships Duringsupporting
confidence: 92%
“…These oocytes have a very limited ability to initiate nuclear maturation in vitro. Similarly, growing Xenopus or starfish oocytes do not respond to progesterone or to l-methyl adenine (Wasserman et al, 1984;Bulet et al, 1985) by resuming meiosis. Since the lack of meiotic response to progesterone by late stage IV Xenopus oocytes is not due to the absence of steroid receptors (Sadler and Maller, 1983), the inability of growing oocytes to resume meiotic maturation may be attributed to the absence of messenger RNAs coding for a cytoplasmic factor, e.g., as the maturation promoting factor (MPF), which was originally described as enabling cytoplasm from progesterone-treated Xenopus oocytes to cause a rapid germinal vesicle breakdown (GVBD) upon microinjection into recipient oocytes (Dettlaff et al, 1964;Masui and Markert, 1971;Smith and Ecker, 1971).…”
Section: Meiotic Competence Is Acquired Duringmentioning
confidence: 99%
“…Maturation-promoting factor (MPF) is generally retained during the metaphase and its disappearance by cyclin degradation triggers the promotion to anaphase (12,13). On the other hand, the polar body formation in a fused oocyte, where an oocyte undergoing GVBD is fused with an immature but fully grown oocyte, takes place one by one (altogether four polar bodies) (2). Since the cytoplasm is common in this case, the timing of appearance and disappearance of MPF must be controlled only around each MA.…”
Section: Morphologymentioning
confidence: 99%
“…Some studies using the cell fusion technique in echinoderm development have been reported (1,2,16,17,22,23). In these studies, fused oocytes or eggs displayed only oocyte maturation (germinal vesicle breakdown) or several divisions.…”
Section: Cell Fusionmentioning
confidence: 99%
“…These naked AEFs were kept until cell fusion on 1% agar-coated plates filled with ASW. : GV-oocytes were exposed to ASW containing nile blue (1 or 2 drops of 1 % nile blue to about 2 ml ASW) for a few min to stain the cortices, in particular the nile blue-positive granules (2,12). Alternatively the entire cytoplasm of other GV-oocytes was stained by keeping them in ASW containing rhodamine B isothiocyanate (RITC, 10 pglml; Sigma) for 1 hr (4).…”
Section: Animals and Oocytesmentioning
confidence: 99%